A highly efficient and reusable MCM-41-immobilized bipyridine copper(i) catalyst for the C–Se coupling of organoboronic acids with diaryl diselenides1. (2nd March 2015) - Zhao, Hong; Jiang, Yuanyuan; Chen, Qiurong; Cai, Mingzhong
<x xml:space="preserve">Abstract</x> A heterogeneous copper-catalyzed cross-coupling reaction of diaryl diselenides with organoboronic acids for the synthesis of diorganyl selenides has been described.